Efecto de la influencia del cambio climático en el cultivo de Banano en el Ecuador - Caravedo Contreras, Bolívar Fernando (2024)
This document deals with the Effect of the influence of climate change on banana cultivation in Ecuador. Climate change is one that affects biogeophysical and socioeconomic processes, causing significant positive and negative repercussions on ecosystems and the environment. society. Banana is one of the most desirable and important crops worldwide due to its nutritional qualities, its export volume, generator of local markets and employment for the rural population. The banana producing countries are Colombia, Ecuador and Costa Rica. Techniques to mitigate these impacts and promote sustainability in banana production The implementation of sustainable agricultural practices can reduce the environmental footprint of banana plantations. The main objective is to describe the effect of climate change on banana cultivation in Ecuador. The methodology was developed and information was collected from updated articles, magazines, blogs, scientific documents, online bibliographic resources, websites, among others. The impacts of climate change, a crucial concern for banana production is the possible appearance of pests and diseases derived from climatic conditions. The conclusion was developed that producers must identify critical points and analyze the factors that affect banana yield and production. The implementation of smart agricultural technologies and the incorporation of efficient irrigation systems is recommended.